Examining Self-Reported Thought Disorder: Continuous Variation, Convergence with Schizotypy, and Cognitive Correlates. (July 2020) - Sumner, Philip J.; Carruthers, Sean P.; Rossell, Susan L.
Highlights: 3 Self-reported thought disorder severities vary continuously across diagnoses 3 Self-reported thought disorder converges with disorganized schizotypy 3 Self-reported thought disorder is associated with semantic and executive function Abstract: When measured from the perspective of a clinician, the severity of 'objective' thought disorder (TD) has been found to vary continuously between people with and without psychosis-related diagnoses, and has been linked with semantic and executive dysfunctions in people with psychosis. Measures of 'subjective' TD that are derived from a first-person perspective have also been produced, but their relationships with objective TD and cognition are unclear. The aims of the current study were: to determine whether responses on a self-report TD questionnaire correspond with responses to a self-report measure of schizotypal disorganization; and to explore the association between these self-reported subjective TD severities and cognitive performance. Data was collected from a sample of 33 people without psychiatric diagnoses and 38 people diagnosed with schizophrenia or schizoaffective disorder evincing mild symptomatology, and this data was pooled for analysis in accordance with the continuum model. Self-reported TD frequencies were associated with the endorsement of disorganized schizotypal experiences. Moreover, self-reported TD frequencies showed relationships with measures of semantic and executive functioning. Thus, at mild severities, self-reported TD shows continuous variation and is associated with altered cognitive function.